1977
DOI: 10.1002/pol.1977.170150319
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of cellulose acetate fibers

Abstract: The photodegradation of cellulose acetate fibers by ultraviolet light in vacuo at 77°K and at ambient temperature was studied. Three kinds of light sources with different wavelengths between 2353 and 6000 Å were employed. ESR studies at 77°K show that several kinds of free radicals are produced from cellulose diacetate (CDA) and cellulose triacetate (CTA) fibers when irradiated with light of wavelength shorter than 2800 Å. Among these methyl radicals formed decayed within 210 min at 77°K. When the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 18 publications
3
34
1
1
Order By: Relevance
“…CA films were placed in glass vials (20 mL, 23 Â 75 mm 2 ) and the vials were sealed with aluminum caps attached by poly(tetrafluoroethylene)/silicon septum, and then they were exposed to light from a xenon arc lamp of 1.5 kW in a fadometer TS-2 (Suga Test Instruments, Tokyo, Japan). The light was filtered at the cut-off value of 275 nm so that the spectra were similar to those from the solar according to the spectra data in the user's manual of the fadometer.…”
Section: Photoirradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…CA films were placed in glass vials (20 mL, 23 Â 75 mm 2 ) and the vials were sealed with aluminum caps attached by poly(tetrafluoroethylene)/silicon septum, and then they were exposed to light from a xenon arc lamp of 1.5 kW in a fadometer TS-2 (Suga Test Instruments, Tokyo, Japan). The light was filtered at the cut-off value of 275 nm so that the spectra were similar to those from the solar according to the spectra data in the user's manual of the fadometer.…”
Section: Photoirradiationmentioning
confidence: 99%
“…[1][2][3] Hon has reported that ultraviolet exposure to CA fibers led to loss of sample weight and acetic acid content. 2 In our previous study using a xenon fadometer for light stability tests, however, CA films showed no detectable acetic acid generation or decrease in the molecular weight by photoirradiation for at least 28 days. 4 Therefore, photodegradation of CA under ambient environment seems to be very slow.…”
Section: Introductionmentioning
confidence: 98%
“…Cellulose acetate has an absorption at approximately 260 nm which is attributed to ketonic carbonyl groups [53]. In consideration of the fact, that the sunlight reaching earth's surface after being filtered by the atmosphere has a lower cut-off of approximately 300 nm, one might conclude that cellulose acetate does not significantly photo degrade in a natural environment.…”
Section: Photo Degradationmentioning
confidence: 99%
“…The studies by Hon [53] provided insight into the mechanisms, which comprises both a polymer chain scission of the glucosidic bond and a cleavage of side groups. Acetate fibers were irradiated in quartz tubes within the ESR cavity under vacuum at 77 K with far UV-light.…”
Section: Degradation By Far Uv-lightmentioning
confidence: 99%
See 1 more Smart Citation